PENINGKATAN PEMAHAMAN WARGA DESA SALBE UNTUK MENJAGA KUALITAS AIR UMBUL SIMARUMBALANG MELALUI KEGIATAN PENYULUHAN KPPM INTEGRATIF - Lidia Sriayu S; Ravic Purba; Wilman Situmorang; Ewin Handoco S (Journal of Research and Publication Innovation, 2025)
Umbul Simarumbalang is one of the water sources that is a mainstay for the residents of Salbe Village. However, despite its great potential, the community's understanding regarding water quality and how to maintain its cleanliness is still limited. The purpose of this activity is to increase the knowledge and awareness of the people of Salbe Village regarding the importance of maintaining the water quality of Umbul Simarumbalang through educational and integrative outreach/socialization activities. The results obtained for three parameters were an average pH of 7.55, for DO with an average value of 9.9, and for an average temperature of 24.6°C. From the results of water quality measurements in Umbul Simarumbalang, it can be concluded that the quality of the water in Umbul Simarumbalang is very good if consumed directly when the weather is not rainy or has not just rained.